68.0k views
2 votes
Expresses the equality of two mathematical expressions.

3x + 3 = 2x + 4

2x + 3y = 2 - 2x

2 Answers

2 votes

Answer:

What. Up. Kyndall

Explanation:

User Carlos Cuesta
by
5.6k points
3 votes

Answer:


x=1


y=(2-4x)/(3)

Explanation:

Given : Mathematical expressions,


3x + 3 = 2x + 4


2x + 3y = 2 - 2x

To find : Expresses the equality of two mathematical expressions ?

Solution :

The equality of mathematical expressions is defined as a relationship between two quantities or asserting that the quantities have the same value.

In expression,
3x + 3 = 2x + 4

Solve the expression,


3x-2x=4-3


x=1

The relationship is that the value of x is 1.

In expression,
2x+3y=2-2x

Solve the expression,


3y=2-2x-2x


3y=2-4x


y=(2-4x)/(3)

The relationship between x and y is
y=(2-4x)/(3)

User Pandora
by
4.9k points